Analysis of Agricultural Land Conversion in Manurung Village, Bola District, Wajo Regency - Isra Yusanda; Muhammad Husain Hasan; Ahmad Hamado (Tinta Emas Institute, 2025)
Conversion of agricultural land is one of the serious problems faced at the rural level, including in Manurung Village, Bola District, Wajo Regency. In fact, in the Wajo Regency Spatial Planning (RTRW) document, the Manurung Village area is designated as an agricultural cultivation area that should be maintained to support food security. However, the reality in the field shows that there is a change in agricultural land use to non-agricultural land that continues to occur. This study aims to analyze the conversion of agricultural land in Manurung Village, Bola District, Wajo Regency, in the period 2014 to 2024. The main focus of the study is: (1) To determine the percentage of changes in agricultural land use in Manurung Village during the period 2014 to 2024, (2) To identify and analyze the factors that drive the conversion of agricultural land in Manurung Village., (3) To analyze the impacts caused by the conversion of agricultural land. The methods used include spatial analysis through interpretation of Google Earth imagery and manual digitization, as well as quantitative statistical analysis using multiple regression to determine the influence of economic, demographic, policy, and socio-cultural factors on land change. The research results show that during the 2014–2024 period, there was a decrease in rice fields by 8.97% and shrubs by 18.49%. Meanwhile, built-up land increased by 76.6%, plantations by 52.63%, and lakes by 17.84%. Economic and demographic factors are the main drivers of land conversion, particularly the need for settlements and non-agricultural economic activities.